2017
DOI: 10.1093/dnares/dsx022
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of Sus scrofa circular RNAs across nine organs and three developmental stages

Abstract: The spatio-temporal expression patterns of Circular RNA (circRNA) across organs and developmental stages are critical for its function and evolution analysis. However, they remain largely unclear in mammals. Here, we comprehensively analysed circRNAs in nine organs and three skeletal muscles of Guizhou miniature pig (S. scrofa), a widely used biomedical model animal. We identified 5,934 circRNAs and analysed their molecular properties, sequence conservation, spatio-temporal expression pattern, potential functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
146
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(183 citation statements)
references
References 77 publications
33
146
4
Order By: Relevance
“…CircRNAs harbor well‐conserved canonical miRNA response elements (MREs), suggesting that some circRNAs act as miRNA sequesters or sponges . A portion of circRNAs are thought to negatively regulate the levels of miRNAs and increase or decrease the expression levels of their corresponding targeted genes (Figure B).…”
Section: Functions Of Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs harbor well‐conserved canonical miRNA response elements (MREs), suggesting that some circRNAs act as miRNA sequesters or sponges . A portion of circRNAs are thought to negatively regulate the levels of miRNAs and increase or decrease the expression levels of their corresponding targeted genes (Figure B).…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“…Circular RNAs are generated from lariat-driven circulation or back-splicing events between the splice donor site of a downstream exon and the splice acceptor site of an upstream exon act as miRNA sequesters or sponges. [17][18][19][20] A portion of cir-cRNAs are thought to negatively regulate the levels of miR-NAs and increase or decrease the expression levels of their corresponding targeted genes ( Figure 2B). As a representative circRNA, cerebellar degeneration-related protein 1 antisense (CDR1as) is the sponge of miR-7 in the embryonic zebrafish and has been reported to be related to brain dysfunction and many cancers, such as HCC and gastric cancer.…”
Section: Mirna Sequestrationmentioning
confidence: 99%
“…, testes (Liang et al 2017b), peripheral whole blood 62 (Memczak et al 2015), peripheral blood mononucleotide cells (Qian et al 2018), platelets 63 (Alhasan et al 2016), and exosomes (Li et al 2015a). CircRNAs have also been related to the 64 development of the fetal human brain (Szabo et al 2015), mouse brain (You et al 2015), fetal 65 porcine brain (Veno et al 2015), and Drosophila neural systems (Westholm et al 2014).…”
mentioning
confidence: 99%
“…CircRNAs are conservatively expressed from orthologous genomic regions between humans and mice (Guo et al, 2014;Jeck et al, 2013) and among Drosophila species (Westholm et al, 2014). Detailed analyses of circRNA expression in humans (Guo et al, 2014;Liu et al, 2016b;Xia et al, 2016), mice (Xia et al, 2016), pigs (Liang et al, 2017b), and flies (Westholm et al, 2014) have revealed substantial tissue-specific patterns of circRNA expression. Notably, circRNAs are enriched and abundantly expressed in some specific tissue types and blood components, such as the brain (Rybak-Wolf et al, 2015;Szabo et al, 2015;Veno et al, 2015;Westholm et al, 2014), testes (Liang et al, 2017b), peripheral whole blood (Memczak et al, 2015), peripheral blood mononucleotide cells (Qian et al, 2017), platelets (Alhasan et al, 2016), and exosomes (Li et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analyses of circRNA expression in humans (Guo et al, 2014;Liu et al, 2016b;Xia et al, 2016), mice (Xia et al, 2016), pigs (Liang et al, 2017b), and flies (Westholm et al, 2014) have revealed substantial tissue-specific patterns of circRNA expression. Notably, circRNAs are enriched and abundantly expressed in some specific tissue types and blood components, such as the brain (Rybak-Wolf et al, 2015;Szabo et al, 2015;Veno et al, 2015;Westholm et al, 2014), testes (Liang et al, 2017b), peripheral whole blood (Memczak et al, 2015), peripheral blood mononucleotide cells (Qian et al, 2017), platelets (Alhasan et al, 2016), and exosomes (Li et al, 2015a). CircRNAs have also been related to the development of the fetal human brain (Szabo et al, 2015), mouse brain (You et al, 2015), fetal porcine brain (Veno et al, 2015), and Drosophila neural systems (Westholm et al, 2014).…”
Section: Introductionmentioning
confidence: 99%